Booming, borrowing, and consuming: the U.S. economy in 1999. - Henwood, Doug (Monthly Review: An Independent Socialist Magazine)
Part of a special issue on capitalism at the end of the millennium in a global context. U.S. economic and political power looks awesome, but the fact that it is brutal, smug, philistine, and heavily financed by foreign lenders does not appear to concern the elites who are celebrating it. It is stretching the truth to call the U.S. economic performance in the 1990s a boom. By the measure of real GDP growth, the 1990s expansion is the slowest of the century—and by a considerable margin. In addition, growth in the U.S. is not quite in the world-class league, as is often claimed: While aggregate growth figures may be flattering the U.S., the per capita figures provide a different account. According to social measures such as income inequality, incarceration rates, and environmental destruction, only Russia, a nation in total collapse, outdoes the U.S. in negative social indicators.